An Investigation of the Theory of Planned Behavior and the Role of Tax Amnesty in Tax Compliance - Agnes Findia Novianti; Nurul Hasanah Uswati Dewi (Universitas Hayam Wuruk Perbanas, 2017)
The individual taxpayers’ low awareness has become the main problem of developing countries in tax aspect. Thus, this study aimed to examine the determinant factors of tax noncompliance using Ajzen’s (1991) Theory of Planned Behavior as a theoretical framework. Specifically, Tax Amnesty is added to the theory’s constructs: attitude, subjective norms, and perceived behavioral control. Tax Amnesty is expected to be a moderating influence. The population of this study is individual taxpayer in KPP Pratama Sukomanunggal. Based on convenience sampling method, the number of sample in this study are 145 samples. The data was analyzed using Structural Equation Modeling (SEM) with SmartPLS.3.0 and SPSS 21. The results indicated that first, attitude and subjective norms are significantly influence behavioral intention except perceived behavioral control. Second, the model including Tax Amnesty provides a significant influence of tax noncompliance in two constructs; attitude and subjective norms. However, the interaction effect of perceived behavioral control does not appear significantly.